Experimenting with governance: the role of power and agency in a network of community-led initiatives - Quintão, F. (13th International Sustainability Transitions Conference, 2022)
Grassroots initiatives have shown relevant contributions to democratic innovation (Smith & Stirling, 2018), experimenting with participatory and deliberative ideas in their inner life, prefiguring alternative forms of democratic politics, and disseminating these ideas within institutions (della Porta, 2022). These social movements frequently seek to unravel the environment-economy dichotomy inherent in contemporary capitalism, directing their action to issues like local food systems, small-scale and alternative energy economies, sustainable communities, and housing (Star, 2020). However, despite having common agendas, they present crucial differences among their discourses regarding themes such as the role of the State, degree of reform or radical innovation, degree of the imaginative character of the sustainability vision, and degree of opposition to capitalism (Feola & Jaworska, 2019). A well-studied social movement that is grounded in the economic imaginary of degrowth is the Transition movement (Longhurst et al., 2017), which started with a local initiative in 2005 in Totnes, UK. Since then, it has spread to over 48 countries with thousands of groups organized in different contexts, such as towns, villages, cities, universities, and schools. Very soon, the movement institutionalized itself as a charity in the UK called Transition Network, which aims to support the movement. For the last four years, the Transition Network has been experimenting with a shared governance model that aims to distribute power, resources, and responsibilities transparently across the international network. However, this experience has not been deeply analysed by scholarly work. Considering that, the objective of this paper is to inquire about the governance of the Transition Network at its different levels (local, national, and international) and between them. Data will be collected by archival research, semi-structured interviews with key actors, and participant observation in the international decision-making instances of the network as well as in national hubs and local initiatives in two countries, Portugal and Belgium. These countries present different cultures of participation, and the network developed following very distinctive pathways. Theoretically, the paper is supported by the Power in Transition Framework (POINT) (Avelino, 2017) and Transition Management (TM) (Avelino & Grin, 2017) to analyse better the transition arena formed around these relationships of the different levels of the network and the governance strategies utilized to influence public institutions and reach regime changes. The paper aims to contribute to two research directions for the agenda of the Governing transition: the application of the ideas of micro-politics, power, and agency in experimentation; and to develop a framework to analyze how experimental governance approaches support transitions (Köhler et al., 2019).